Efficient de novo assembly of highly heterozygous genomes from whole-genome shotgun short reads - Kajitani, Rei; Toshimoto, Kouta; Noguchi, Hideki; Toyoda, Atsushi; Ogura, Yoshitoshi; Okuno, Miki; Yabana, Mitsuru; Harada, Masayuki; Nagayasu, Eiji; Maruyama, Haruhiko; Kohara, Yuji; Fujiyama, Asao; et al. (Genome Research, 2014)
Although many de novo genome assembly projects have recently been conducted using high-throughput sequencers, assembling highly heterozygous diploid genomes is a substantial challenge due to the increased complexity of the de Bruijn graph structure predominantly used. To address the increasing demand for sequencing of nonmodel and/or wild-type samples, in most cases inbred lines or fosmid-based hierarchical sequencing methods are used to overcome such problems. However, these methods are costly and time consuming, forfeiting the advantages of massive parallel sequencing. Here, we describe a novel de novo assembler, Platanus, that can effectively manage high-throughput data from heterozygous samples. Platanus assembles DNA fragments (reads) into contigs by constructing de Bruijn graphs with automatically optimized k-mer sizes followed by the scaffolding of contigs based on paired-end information. The complicated graph structures that result from the heterozygosity are simplified during not only the contig assembly step but also the scaffolding step. We evaluated the assembly results on eukaryotic samples with various levels of heterozygosity. Compared with other assemblers, Platanus yields assembly results that have a larger scaffold NG50 length without any accompanying loss of accuracy in both simulated and real data. In addition, Platanus recorded the largest scaffold NG50 values for two of the three low-heterozygosity species used in the de novo assembly contest, Assemblathon 2. Platanus therefore provides a novel and efficient approach for the assembly of gigabase-sized highly heterozygous genomes and is an attractive alternative to the existing assemblers designed for genomes of lower heterozygosity.